Disney ideas book - Dowsett, Elizabeth (New York DK Publishing, 2018)
"Let your imagination run wild with Disney arts and crafts, party games, puzzles, and papercraft. With magical projects for every level of ability and clear, step-by-step, illustrated instructions, you will never be bored again! Build Cinderella's castle, take off with Buzz Lightyear's wings, dress up in Moana's flower crown, play Snow White bowling, race Lightning McQueen on your own racetrack, and much, much more." --
Find Your Favorites -- Before You Begin -- Make-believe Flower Crown -- Cardboard Car Costumes -- Cardboard Candelabra -- Rags-to-Riches Apron -- Felt Animal Masks -- Miguel's Guitar -- Selfie Props -- Salt-Dough Necklace -- Elsa's Sparkly Cape -- Playing-Card Costumes -- Pirate Hook -- Animal-Feet Stilts -- Shark Cap -- Cupcake-Liner Lei -- Buzz Lightyear's Wings -- Felt Finger Puppets -- Fairy Garden -- Felt Ears -- Pumpkin Coach -- Games Kiss the Frog -- Flamingo Croquet -- Seven Dwarfs Pins -- Which Sidekick Are You? -- Echolocation -- Musical Flying Carpets -- Dogcatcher -- Tigger Races -- Sleeping Beauties -- Catch the Rat -- Pooh Sticks -- Fox and Hound Chase -- 101 Dalmatians Game -- Parachuting Soldiers -- Mulan's Training Camp -- Apple Bobbing -- Toys Come Alive -- Who Am I? -- Untangled -- Memory Game -- Archery Competition -- Test Your Knowledge! -- Art Mickey String Decoration -- Story Stones -- Button Art -- Paint-Splatter Fireworks -- Papel Picado -- Personalized Letters -- Handprint Fish -- Stained-Glass Windows -- Pixel Art -- Concertina Cards -- Abstract Art -- Sliding Image -- Balloon Faces -- Slotted Sculptures -- Activities Grass-Hair Trolls -- Mushu Shadow Puppet -- Scavenger Hunt -- Create a Secret Club -- Ursula's Bath Bombs -- Baymax Origami -- Fairy-Tale Castle -- Paper Planes -- Shoebox Theater -- Levitation Trick -- Constellation Jar -- Belle's Book Garland -- Will o' the Wisps -- Zoetrope -- Boogie with Baloo -- Teacup Races -- Sing-Off -- Pixie-Dust Lip Gloss -- Glow-in-the-Dark Stars -- Soda Volcano -- Piston-Cup Racetrack -- Raft Building -- g Craft Clothespin Mermaids -- Paper Elephant Parade -- Hamm Piggy Bank -- Snowgie Snowflakes -- Enchanted Rose Glitter Jar -- Covered Notebooks -- Heroic Bookends -- Painted Eggs -- Paper-Clip Friends -- Party Straws -- Party Hats -- Party Bags -- Printed Gift Wrap -- Party Paper Chains -- Carrot Pen -- Rapunzel Bookmark -- Monster Pom-Poms -- Charm Bracelets -- Memory Spheres -- Barrette Organizer -- Friendship Necklaces -- Recycled Robot -- Egg-Carton Bugs -- Olaf Sock Toy -- Templates
Arts (handcrafts)
1 2
Keywords: Walt Disney Productions -- Juvenile literature; Walt Disney Productions; Walt Disney Productions -- Juvenile literature; 101 Dalmatians (Motion picture) -- Juvenile literature; Aladdin (Motion picture) -- Juvenile literature; Alice in Wonderland (Motion picture) -- Juvenile literature; Aristocats (Motion picture) -- Juvenile literature; Big Hero 6 (Motion picture) -- Juvenile literature; Brave (Motion picture) -- Juvenile literature; Bug's life (Motion picture) -- Juvenile literature; Cars (Motion picure) -- Juvenile literature; Cinderella (Motion picture) -- Juvenile literature; Coco (Motion picture) -- Juvenile literature; Dumbo (Motion picture) -- Juvenile literature; Elena of Avalor (Motion picture) -- Juvenile literature; Finding Dory (Motion picture) -- Juvenile literature; Finding Nemo (Motion picture) -- Juvenile literature; Fox and the hound (Motion picture) -- Juvenile literature; Frozen (Motion picture) -- Juvenile literature; Good dinosaur (Motion picture) -- Juvenile literature; Hercules (Motion picture) -- Juvenile literature; Hunchback of Notre Dame (Motion picture) -- Juvenile literature; Incredibles (Motion picture) -- Juvenile literature; Inside Out (Motion picture) -- Juvenile literature; Jungle Book (Motion picture) -- Juvenile literature; Lady and the Tramp (Motion picture) -- Juvenile literature; Lilo & Stitch (Motion picture) -- Juvenile literature; Lion King (Motion picture) -- Juvenile literature; Little Mermaid (Motion picture) -- Juvenile literature; Micky and Friends (Motion picture) -- Juvenile literature; Moana (Motion picture) -- Juvenile literature; Monsters University (Motion picture) -- Juvenile literature; Mulan (Motion picture) -- Juvenile literature; Peter Pan (Motion picture) -- Juvenile literature; Pinocchio (Motion picture) -- Juvenile literature; Planes (Motion picture) -- Juvenile literature; Pocahontas (Motion picture) -- Juvenile literature; Princess and the frog (Motion picture) -- Juvenile literature; Rataouille (Motion picture) -- Juvenile literature; Sleeping Beauty (Motion picture) -- Juvenile literature; Snow White and the seven dwarfs (Motion picture) -- Juvenile literature; Tangled (Motion picture) -- Juvenile literature; Tigger movie (Motion picture) -- Juvenile literature; Tinker Bell (Motion picture) -- Juvenile literature; Toy story (Motion picture) -- Juvenile literature; Up (Motion picture) -- Juvenile literature; WALL-E (Motion picture) -- Juvenile literature; Winnie the Pooh (Motion picture) -- Juvenile literature; Wreck-It Ralph (Motion picture) -- Juvenile literature; Zootopia (Motion picture) -- Juvenile literature; Games -- Juvenile literature; Games; Handicraft -- Juvenile literature; Handicraft; Games; Handicraft; Juvenile works